2016
DOI: 10.1016/j.cell.2016.08.056
|View full text |Cite
|
Sign up to set email alerts
|

Editing DNA Methylation in the Mammalian Genome

Abstract: SUMMARY Mammalian DNA methylation is a critical epigenetic mechanism orchestrating gene expression networks in many biological processes. However, investigation of the functions of specific methylation events remains challenging. Here, we demonstrate that fusion of Tet1 or Dnmt3a with a catalytically inactive Cas9 (dCas9) enables targeted DNA methylation editing. Targeting of the dCas9-Tet1 or -Dnmt3a fusion protein to methylated or unmethylated promoter sequences caused activation or silencing, respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
842
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 991 publications
(855 citation statements)
references
References 57 publications
11
842
1
1
Order By: Relevance
“…18,19,21,22 TET enzymes mediate DNA demethylation indirectly through oxidation of 5mC to 5hmC, and further oxidation of 5hmC to 5fC and 5caC. 29,30 However, bisulfite sequencing does not distinguish between unmethylated C and either 5fC or 5caC, since these two derivatives are not resistant to deamination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19,21,22 TET enzymes mediate DNA demethylation indirectly through oxidation of 5mC to 5hmC, and further oxidation of 5hmC to 5fC and 5caC. 29,30 However, bisulfite sequencing does not distinguish between unmethylated C and either 5fC or 5caC, since these two derivatives are not resistant to deamination.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Recent studies have shown targeted DNA demethylation and gene reactivation in mammalian cells by fusing different enzymes involved in DNA demethylation to diverse DBDs. [18][19][20][21][22] However, no efforts have been reported so far to express or target plant 5mC DNA glycosylases, which directly excise 5mC from DNA.…”
Section: Introductionmentioning
confidence: 99%
“…2b). Similarly, fusion of histone or DNA methyl transferases to Cas9 has been used to prove the influence of specific DNA methylation events 61, 62, 63, 64, 65, 66.…”
Section: Dna Methylation and Demethylationmentioning
confidence: 99%
“…Tethering the catalytic domain of the DNA demethylase Tet1 to dCas9 has been used for targeted DNA demethylation (Figure 4a). These fusions can induce over 90% demethylation of CpG islands within a 200-bp range of the target site Morita et al, 2016;Liu et al, 2016). Researchers have also developed a histone-modifying CRISPR-based tool in which the catalytic domain of human acetyltransferase p300 was fused to the C-terminus of dCas9.…”
Section: Epigenome Editingmentioning
confidence: 99%